Role of low dose danazol therapy for endometriosis related infertility and its comparison with laparoscopic fulguration in low resources - Verma, Urvashi; Singh, Shivani; Chandra, Mukesh; Singh, Richa; Chandra, Mukul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The objective was to study the role of laparoscopic fulguration and danazol therapy for endometriosis in case of infertility followed by comparison of both therapies. Methods: The present cross–sectional study was conducted in the department of obstetrics and gynecology SN Medical College Agra. Over the period from December 2010 to November 2013. Symptomatic women (n=50) of age group 20-39 yrs coming to gynecology OPD were selected for study group. The study group was subjected to detailed history, physical examination laboratory test, ultrasound examination, and laparoscopy. Then 50 patients were allotted for laparoscopic fulguration and 50 for danazol treatment. Results: Out of 100 on transvaginal sonography, 10%of patient have cyst <2cm size and 20% have >2cm size, rest 70% have normal scan. On laparoscopy 52% of patient have red lesion, 16% have bluish black lesion, 20% have yellow brown lesion rest 22% have normal findings. On danazol therapy pelvic pain and dysmenorrhoea was relieved in 64% and 52% conceived .on laparoscopic fulguration symptom were relieved in 69% and 60% conceived. Conclusions: Based on this study it can be concluded that choice of therapy depend on age of patient, duration of infertility, physical findings, goal of surgery, experience of surgeon and most important the availability of resources. In this study result was comparable.